2017
DOI: 10.5513/jcea01/18.4.1963
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition of meat and genetic mapping of quantitative trait loci in 3 generations of Japanese quail populations

Abstract: The present study was carried out to evaluate the effect of different lines and generations of adult males and females of Japanese quail (Coturnix japonica) on total lipid, fatty acid (FA) composition and cholesterol content of breast muscle, as well as the identification of quantitative trait loci (QTLs) controlling the above mentioned meat quality traits. Forty-four quails (generation F 0 ), 22 Pharaoh (F-33) meat-type males and 22 Standard (S-22) laying-type females, were crossed to produce the F 1 hybrids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…The h/H ratio and the AI were not significantly influenced ( P > 0.05) by neither the quail species nor by the origin within CQ. The results observed herein on farmed quail fatty acid ratios and lipid quality indices are within the range of values previously presented by Tavaniello et al (2017) .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The h/H ratio and the AI were not significantly influenced ( P > 0.05) by neither the quail species nor by the origin within CQ. The results observed herein on farmed quail fatty acid ratios and lipid quality indices are within the range of values previously presented by Tavaniello et al (2017) .…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, significant difference ( P = 0.031) on breast meat total cholesterol was observed between wild and farmed specimens within CQ, farmed specimens presented a superiority of 12.9% on the total cholesterol content (more 8.32 mg/g of meat). The total cholesterol content observed in quail's breast meat obtained from farmed quails (71.1–72.7 mg/100 g of meat) is inside the range of cholesterol content previously presented in quail's breast meat (67.2–76 mg/100 g of meat) for domestic quails ( Coturnix japonica ) ( Ioniţă et al, 2010 ; Fakolade, 2015 ; Tavaniello et al, 2017 ; Cullere et al, 2018 ). Whereas, the total cholesterol content observed in wild CQ (64.4 mg/100 g of meat) is quite below that range, but we found no comparison for it.…”
Section: Resultssupporting
confidence: 74%
“…Regardless of the treatment, the effect of the line variation on nutritional composition was insignificant. A similar trend was also reported by Tavaniello et al (2017) who found no effect of different lines of Japanese quail on breast muscle total lipid content and fatty acid profiles. Repeated measures analysis showed no significant (P>0.05) diet × line interaction effect on nutritional composition of breast and thigh meat proximate composition and omega-3 and omega-6 (Table 4 and 5).…”
Section: Resultssupporting
confidence: 90%
“…Moreover, the atherogenic index (AI) and the thrombogenic index (TI) were calculated 26 . Method used for fatty acid composition were done in the same way as it was described by Tavaniello et al 33 .…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
“…The quantitation of cholesterol content in muscles was based on the external standard method using a pure cholesterol standard (Sigma, St. Louis, MO). This method was also done according to the method of Tavaniello et al 33 .…”
Section: Fatty Acid Compositionmentioning
confidence: 99%